EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK MODELING UNTUK MENINGKATKAN PERENCANAAN KARIR SISWA KELAS XI MAN KOTA CIMAHI - Agustina, Yanda Rahma; Septian, Muhammad Rezza; Permana, Aditya (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This research was conducted on class XI IPS 2 MAN Cimahi City students in the 2023/2024 academic year. The aim is to improve students' career planning through group guidance services provided using modeling techniques, the method used is a mix method or a method that combines quantitative and qualitative data research. With a sequential explanatory design, the data collection technique used for quantitative research is using a distribution in the form of a questionnaire. Meanwhile, for collecting qualitative data, we used observation guidelines and interview guidelines with the guidance and counseling teacher and 2 students of class XI IPS 2. The research subjects were 10 students in the low category. The results of this research were carried out with a significance value (2-tailed) of 0.002 <0.05. There has been a significant increase in group guidance services to improve student career planning. The obstacle faced during the writing process was time constraints considering that there were no special hours for counseling guidance services.